Pemberdayaan Pendidikan Dalam Mengantisifasi Permasalahan Kehidupan Masyarakat Modern - Panji Ahmad Syuhada; Syahbuddin . (AL-QOLAM : Jurnal Dakwah dan Pemberdayaan Masyarakat, 2017)
demands, suggestions) by the subject of education to the development of the soul (mind, feeling, willingness and intuition) and the body of the object students with certain materials, at certain time, with a particular method with tools the existing equipment to the creation of a particular person with evaluation according to the teachings of Islam, therefore, the goal of Islamic education is inseparable from the purpose of human life in Islam; creating a personal servant of God who always cautious of Him, and can achieve a happy life in the world and in the heart. In this socio-societal context, these pious nations and personalities can be a blessing of Lil Alamin, both small and large. The purpose of human life in Islam is what can be called as the ultimate goal of Islamic education.Thus, "education is the best means of creating a new generation of young people who will not close ties with their own traditions but at the same time not to become intellectually stupid or backward in their education or unaware of the developments in every branch of human knowledge" (Conference Book, London, 1978: 15-17).In this paper, we will try to reveal some matters relating to the objective condition of modern society's education today, and how to anticipate the problematic life of modern society in the future, so that Islamic education can develop the quality of education and how the efforts of Islamic education can design in fulfilling the needs an ever-changing society.